DOI: 10.24124/2001/bpgub174
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale behavioural approach to understanding the movements of woodland caribou.

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon th e quality of the copy subm itted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 191 publications
(368 reference statements)
0
34
0
Order By: Relevance
“…Completion of this project and corresponding accuracy assessment allowed us to control the development and evaluate the vegetation maps to which we ascribed considerable importance in interpreting caribou movements and habitat affinities (Johnson, 2000). Evaluation and control were important considerations that weighed heavily in our decisions to pursue this project.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Completion of this project and corresponding accuracy assessment allowed us to control the development and evaluate the vegetation maps to which we ascribed considerable importance in interpreting caribou movements and habitat affinities (Johnson, 2000). Evaluation and control were important considerations that weighed heavily in our decisions to pursue this project.…”
Section: Resultsmentioning
confidence: 99%
“…Combinations were based upon errors of commission (i.e. cover types that were inclusive within another class), our knowledge of caribou-habitat relations (Johnson, 2000), and the observed ecological similarities between the 27 identified cover types. Where possible, we attempted to maintain the singularity of those cover types with known relevance to caribou biology (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examine forage selection across scales because previous studies demonstrated ungulates can adopt selection strategies at more than one scale (Wilmshurst et al 1999, Johnson et al 2002, Boyce et al 2003, and adopt Johnson's (1980) hierarchy of scales of selection to guide our analyses.…”
Section: Multi-scale Predictions Of the Forage Maturation Hypothesismentioning
confidence: 99%
“…Location accuracy is inversely related to dilution of precision values, and 3D locations have a higher probability of being more accurate than 2D locations (Trimble Navigation Ltd 1994*; British Columbia Ministry of Environment, Lands and Parks 1995*; Johnson 2000). Whenever GPS location success is <100%, then GPS locations likely represent a biased sample of habitat use because location success is affected by factors like tree density, canopy cover and topography (Rempel et al 1995;Moen et al 1996;Dussault et al 1999;D'Eon et al 2002).…”
Section: Capture and Telemetrymentioning
confidence: 99%